Using the service desk to secure the organisation. Issue 1 (January 2018) - Smith, Kevin
Abstract : Shadowy hackers and cyber-spies tend to dominate the public perception of online threats. Accompanied by clichéd stock images of grim-looking figures wearing face masks and oversized hoodies, they make for great headlines and an over-simplified metaphor to help the public understand the growing cyber-threat landscape. However, the more mundane reality is that – whether directly or indirectly – your everyday employees are the source of most threats to the organisation. The question is, what can we do to mitigate the risk of the insider threat Your employees are the source of most threats to the organisation. The question is, what can we do to mitigate the risk? The key is to bring together relevant IT and security teams united through the actions of an empowered service desk. You'll get better at detecting the early warning signs of a serious threat and proactively securing your endpoints. This kind of preventative approach could end up saving you millions in breach-related losses, argues Kevin Smith of Ivanti.